Ex-ante Equity Risk Premia: Expectational Estimates Using Stock Market Returns Forecasts in the Emerging Equity Market - Naumoski, Aleksandar; Nestorovski, Metodija (Panoeconomicus, 2018)
We estimated the ex-ante equity risk premium for the Republic of Macedonia, which is a young, small and open emerging market. We polled academics and practitioners for their expectations on the stock market index MBI10 as a proxy for market portfolio. The risk premium is the expected MBI10 return relative to a government bond yield. Using the Kolmogorov–Smirnov and Anderson–Darling goodness-of-fit tests we determined the best fitted statistical distribution, and consequently estimated the short-term ERP of 8.55 and long-term average ERP for the next 10 years of 7.76. The estimated ex-ante ERP is higher and similar as it is in the other emerging markets.Key words: Emerging markets, Forecast, Market returns, Risk-free rate, Expected equity risk premium, Goodness-of-fit test.JEL: G11, G12, G14, G31.Ex-ante rizik premije kapitala: Očekivanja na osnovu prognoza berzanskih premija na tržištu kapitala u razvojuProcenili smo ex-ante premiju rizika kapitala za Republiku Makedoniju, koja je mlado, malo i otvoreno tržište u razvoju. Profesore i praktičare smo anketirali za očekivanja u vezi indeksa MBI10 kao približnu varijablu za tržišni portfolio. Premija rizika je očekivana vrednost povraćaja MBI10 u odnosu na prinos državne obveznice. Korišćenjem testova adekvatnosti Kolmogorov-Smirnov i Anderson-Darling utvrdili smo najbolju statističku raspodelu, a samim tim procenili kratkoročni ERP od 8.55 i dugoročni prosek ERP u narednih 10 godina od 7.76. Procenjeni ex-ante ERP je veći i sličan kao što je to na drugim tržištima u razvoju.Ključne reči: Tržišta u razvoju, predviđanje, povraćaj na tržištu, stopa bez rizika, očekivana premija rizika kapitala, test adekvatnosti.